HEALTH LITERACY ACROSS THREE DOMAINS AND SOCIO-DEMOGRAPHIC DETERMINANTS IN A NON-COMMUNICABLE DISEASE POPULATION IN EASTERN BOLAANG MONGONDOW DISTRICT: A CROSS SECTIONAL STUDY - Ake Royke Calvin Langingi; Grace Ireine Viodyta Watung; Meylani Dewi Wowor; Zefania Ireyne Pagayang; Stella Rasu (PT. Jurnal Center Indonesia Publisher, 2025)
This study aimed to obtain information about socio-demographic factors associated with HL of NCD patients in East Bolaang Mongondow Regency. The method used was quantitative method with cross sectional study design with a total sample of 383 NCD patients (purposive sampling) with stratified sampling technique. Data were collected using questionnaires both socio and demographics and HL of NCD patients. The results of this study were [education (p=0.023, OR=2.711); gender (p=0.017, OR=2.001); language (p=0.001, OR=1.013); age (p=0.020, OR=2.968); employment status (p=0.001, OR=1.248); residence (p=0.012, OR=2.068); personal health condition (p=0.031, OR=5.840); access to health information (p=0.020, OR=2.968). In the logistic regression test, the personal health condition factor was most associated with HL of NCD patients (p=0.010, OR=5.840). In conclusion, the study showed that socio-demographic factors (education, gender, language, age, employment status, residence, personal health condition and access to health information simultaneously or partially influenced the HL of patients with NCDs. The most dominant factor associated with HL of patients with NCDs was personal health conditions. The role of health workers provides many sources of information to develop and learn solutions and support for people with various types of NCDs.